Efforts to Improve Indonesian Learning Achievement in Reading Materials Using the Role-Playing Method in Class XI of the Special State School of Trustees in the Province of East Kalimantan - Widayati, Harni (PT Literasi Nusantara Publisher, 2022)
Child with Intellectual Disability (ID) is a child below average intelligence, experiences behavioural obstacles, adjustments and occurs during his development. Children’s with Intellectual Disability are often equated with mentally retardation terms (Feeble Minded). Reading using the role-playing method is one of the main lessons that teachers give to children at school. The lesson, which is a part of Bahasa course, is given early as a basis for further learning. Children who cannot read yet have difficulty following other lessons. The purpose of this classroom action research is entitled